2018
DOI: 10.1016/j.chemosphere.2018.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Towards practical indoor air phytoremediation: A review

Abstract: Indoor air quality has become a growing concern due to the increasing proportion of time people spend indoors, combined with reduced building ventilation rates resulting from an increasing awareness of building energy use. It has been well established that potted-plants can help to phytoremediate a diverse range of indoor air pollutants. In particular, a substantial body of literature has demonstrated the ability of the potted-plant system to remove volatile organic compounds (VOCs) from indoor air. These find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 142 publications
(239 reference statements)
0
47
0
1
Order By: Relevance
“…These systems use natural bioagents (plants and/or microorganisms) to remove pollutants from the air through an aerobic process, where the pollutants act as energy, carbon, and other nutritional sources for the bioagents, or are otherwise absorbed into or adsorbed on to the biological materials (Wei et al 2017). Additionally, these systems can use substrates containing a proportion of activated carbon and a range of other materials, to assist with pollutant filtration or substrate microbial growth (Pettit et al 2018. The efficiency with which biofilters can filter out and degrade VOCs from indoor air indicates that they may be used to reduce inhabitant pollutant exposure (Sriprapat and Thiravetyan 2013, Wolverton et al 1984, Brilli et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…These systems use natural bioagents (plants and/or microorganisms) to remove pollutants from the air through an aerobic process, where the pollutants act as energy, carbon, and other nutritional sources for the bioagents, or are otherwise absorbed into or adsorbed on to the biological materials (Wei et al 2017). Additionally, these systems can use substrates containing a proportion of activated carbon and a range of other materials, to assist with pollutant filtration or substrate microbial growth (Pettit et al 2018. The efficiency with which biofilters can filter out and degrade VOCs from indoor air indicates that they may be used to reduce inhabitant pollutant exposure (Sriprapat and Thiravetyan 2013, Wolverton et al 1984, Brilli et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the levels of chemical and air pollution have increased due to the extensive use of decorative materials . Many buildings are designed and built with a compact construction, resulting in the indoor pollutants being unable to be discharged in a timely manner . A large quantity of pollutant accumulates in the interior, seriously affecting the indoor air quality and harming human health .…”
Section: Introductionmentioning
confidence: 99%
“…Despite these benefits, it has been suggested that in some cases, plants may compromise the air quality as their emission of biogenic VOCs interacts with urban NOx to produce ozone [23]. Nonetheless, fusing the removal mechanisms of the plant foliage with biofiltration technology to create active green walls (botanical biofilters) has proven to be an efficient means for the removal of other gaseous pollutants, primarily different species of VOCs [24], however, it is unknown whether botanical biofilters are capable of filtering NO x , and what implications this may have for the ambient O 3 concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Active green walls are a green technology that can simultaneously treat a large number of air pollutants at a relatively low cost. This technology builds upon the vast literature purporting the air phytoremediation potential of potted plants ( [24,[26][27][28], plus references therein). Whilst pollutant reduction by potted plants has been well described, for in situ use, such systems will be severely limited in their efficacy [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation